2003
DOI: 10.1161/01.str.0000102171.91292.dc
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and the Risk of Ischemic Stroke

Abstract: Background and Purpose-Large epidemiological studies have not established cholesterol levels as a risk factor for ischemic stroke, but recent clinical trials have demonstrated a reduction in the ischemic stroke rate for patients taking HMG-CoA reductase inhibitors ("statins"). The goal of this study was to evaluate whether total cholesterol (TC), high-density lipoprotein (HDL), triglycerides, and the TC:HDL ratio are risk factors for ischemic stroke in apparently healthy men enrolled in the Physicians' Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 44 publications
6
98
0
4
Order By: Relevance
“…In our study , there was no significant difference between the age groups .regarding hypertriglyceridemia (19% of group A, 28% of group B and 9% of group C) .This was in agreement with Bowman et al (40) ;They found no correlation between non fasting triglycerides and ischemic stroke was found. In another case-control study conducted by Sridharan et al (41) fasting triglyceride level were studied in 204 patients with acute ischemic stroke and 204 controls, they did not find any significant association between fasting triglycerides and acute ischemic stroke.…”
Section: (32)supporting
confidence: 92%
“…In our study , there was no significant difference between the age groups .regarding hypertriglyceridemia (19% of group A, 28% of group B and 9% of group C) .This was in agreement with Bowman et al (40) ;They found no correlation between non fasting triglycerides and ischemic stroke was found. In another case-control study conducted by Sridharan et al (41) fasting triglyceride level were studied in 204 patients with acute ischemic stroke and 204 controls, they did not find any significant association between fasting triglycerides and acute ischemic stroke.…”
Section: (32)supporting
confidence: 92%
“…Shahar et al [15], Bowman et al [16] reported the lack of association between lipids and stroke. Study conducted by Bowman et al, of 296 stroke patients and the same number of controls, found that levels neither of total cholesterol, triglycerides nor HDL were associated with risk of ischemic stroke, although a high total cholesterol/HDL ratio was found to increase the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cholesterol levels in stroke patients have revealed results varying from insignificant changes to a moderate elevation [14]. There are several studies which have not found any association between lipid profile and incident ischemic stroke [15,16]. The aim of this study was to delineate the reliability and accuracy of serum lipid profile in assessing the prognosis/neurological worsening in patients with ischemic and hemorrhagic cerebrovascular stroke.…”
Section: Introductionmentioning
confidence: 94%
“…In stroke, measuring low-density lipoprotein (LDL) and high-density lipoprotein cholesterol or electrocardiogram changes can provide important information regarding risk. [45][46][47][48][49][50] Changes in these measures in response to therapy can reliably alter the risk. For example, converting atrial fibrillation to normal sinus rhythm will reduce the risk of stroke.…”
Section: Predicting Prognosismentioning
confidence: 99%